"SOME CAUSES AND FACTORS OF CONFLICTS IN THE EDUCATIONAL PROCESS" (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes some of the objective and subjective causes of conflict in the educational process. At the same time, pedagogical conflicts and the factors and stages of their resolution are covered.